Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.jhep.2018.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cell therapy for liver diseases

Abstract: The therapeutic potential of mesenchymal stromal cells (MSCs) in the treatment of liver fibrosis is predominantly based on their immunosuppressive properties, and their ability to secrete various trophic factors. This potential has been investigated in clinical and preclinical studies. Although the therapeutic mechanisms of MSC transplantation are still not fully characterised, accumulating evidence has revealed that various trophic factors secreted by MSCs play key therapeutic roles in regeneration by allevia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
148
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(164 citation statements)
references
References 152 publications
3
148
0
3
Order By: Relevance
“…However, a shortage of liver donors greatly limits liver transplantation (1). Recent studies and clinical trials have confirmed that MSC transplantation can be a potential alternative for such liver diseases (5). In our present study, we confirmed that MSCs attenuated ALF via secreting PGE 2 to promote hepatocyte proliferation.…”
Section: Discussionsupporting
confidence: 81%
“…However, a shortage of liver donors greatly limits liver transplantation (1). Recent studies and clinical trials have confirmed that MSC transplantation can be a potential alternative for such liver diseases (5). In our present study, we confirmed that MSCs attenuated ALF via secreting PGE 2 to promote hepatocyte proliferation.…”
Section: Discussionsupporting
confidence: 81%
“…In the subgroup, according to the cut-off value of NLR, statistically significance was found respectively in NLR = 5.0 (HR = 1.74, 95% CI: 1.44-2.11), 2.5 � NLR <5 (HR = 1.69, 95% CI: 1.50-1.91), and NLR < 2.5 (HR = 2.06, 95% CI: 1.77-2. 40). Surprisingly, in the NLR = 5.0 subgroup, the result indicated high statistical heterogeneity with an I 2 value of 77% (P = 0.01), whereas no significant heterogeneity between studies was found in subgroup 2.5 � NLR < 5 and subgroup NLR < 2.5, suggesting that NLR cut-off value for each study may be the source of heterogeneity of the pooled analysis.…”
Section: The Prognostic Value Of Preoperative Nlr For Osmentioning
confidence: 76%
“…With recent advancements and research-related cell therapies, mesenchymal stem cell (MSC) have demonstrated improved clinical applications because of their accessibility, expandability, and multipotentiality [6]. Various MSCs have been transplanted for the treatment of liver cirrhosis [7,8]. Recently, the positive influence of MSCs transplantation has been reaffirmed against alcoholic cirrhosis (AC), including clinical trials for autologous bone marrow-derived mesenchymal stem cell (BM-MSC) transplantation to patients with AC, that have shown the affirmative response of MSCs to reduce liver cirrhosis and improve liver function.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic potentials of MSCs include their immunosuppressive properties, their ability to secrete various trophic factors and hepatic regeneration [8,12]. After the homing of MSCs to at injured tissue sites for repair, when in contact with local stimuli, such as inflammatory cytokines and ligands of toll-like receptors (TLRs), these stimuli can trigger MSCs to release a broad spectrum of bioactive molecules related with tissue remodeling and regeneration [10].…”
Section: Introductionmentioning
confidence: 99%